KANDUNGAN ANTIOKSIDAN ASAM ASKORBAT PADA BUAH-BUAHAN TROPIS - Febrianti, Novi (Program Studi Biologi FMIPA Universitas Mataram, 2016)
Tropical fruits are rich in nutrients and phytochemicals that benefit our health. As source ofantioxidant, regular consumption of fruits will be useful in avoiding many degenerative diseasesparticularly caused by free radicals. The good effects of antioxidants vary from repairing tissuedamages in respiratory system, excretory system as well as reproductive system. Ascorbic acid is onepotent antioxidant that has been recorded for history. Known as Vitamin C, its concentration in fruitshas been a primary consideration for people to choose what kind of fruit they are going to consume.This experimentâs result exhibited different levels of ascorbic acid in some tropical fruits. Averageconcentration of ascorbic acid from the highest to lowest was obtained in avocado,orange, strawberry,guava, apple, papaya, tamarind and mango with their contents of 119,8; 96,8; 66,65; 49,86; 49,57; 48,4and 41,06 mg/100g, respectively. This result would be a baseline in setting the best fruit combinationto obtain maximum effects of antioxidant.Keywords: tropical fruits, antioxidants, ascorbic acid